Insight into catalyst speciation and hydrogen co-evolution during enantioselective formic acid-driven transfer hydrogenation with bifunctional ruthenium complexes from multi-technique operando reaction monitoring. (16th September 2019) - Berry, Daniel B. G.; Codina, Anna; Clegg, Ian; Lyall, Catherine L.; Lowe, John P.; Hintermair, Ulrich
Abstract : Operando spectroscopy shows a transition from dehydrogenation to hydrogen transfer during the reaction, and allows measuring optimal conditions for maximum rate and efficiency. Abstract : Transfer hydrogenation of acetophenone from formic acid/triethylamine mixtures catalysed by the Ikariya–Noyori complex [(mesitylene)RuCl( R, R )-(TsDPEN)] has been investigated using simultaneous high-resolution FlowNMR and FlowUV-Vis spectroscopies coupled with on-line sampling head-space mass spectrometry and chiral high-performance liquid chromatography using an integrated, fully automated recirculating flow setup. In line with previous observations, the combined results show a gradual switch from formic acid dehydrogenation to hydrogen transfer mediated by the same Ru-hydride complex, and point to a Ru-formate species as the major catalyst intermediate. Hydrogen bonding in the formic acid/triethylamine mixture emerges as a sensitive 1 H NMR probe for the transfer hydrogenation activity of the system and can be used to locate optimum reaction conditions.